THE USE OF TALKING STICK TO IMPROVE STUDENTS’ SPEAKING SKILL (A CLASSROOM ACTION RESEARCH ON X MIA-2 STUDENTS OF SMA NEGERI 1 KESAMBEN) - FEBRYANTI, DITA INDRA (Jurnal Ilmiah Mahasiswa FIB, 2015)
Keywords: speaking skill, talking stick, narrative text.In Indonesia,English is considered as a foreign language.Itis just taught in formal education, but it is not used for communication in real context. Speaking is the most important skill in English language learning, since language learners are regarded to be successful if they can communicate fluently. Based on the preliminary study that has been conducted by researcher, it confirmed that most of X MIA-2students of SMA Negeri 1 Kesamben found difficulties in speaking. Regarding to this phenomenon, researcher proposed a teaching technique named talking stick to improve students’ speaking skill. The objective of the research is to describe how talking stick can improve students’ speaking skill of X MIA-2 students of SMA Negeri 1 Kesamben.By using classroom action research design, researcher implemented talking stick to solve the students’ problem in speaking skill. The talking stick is used in teaching narrative text. Researcher uses recorded oral test, questionnaire, interview guide, observation checklist and field note as the instruments. This research was conducted in one cycle that consists of three meetings.The result of the research showed that there is a significant improvement of students’ speaking skill afterthe implementation of talking stick. The improvement can be seen from the achievement of the two criteria of success. The first criterion is if the students’ mean score of post-test gain more than 5 points from the students’ mean score of pre-test. It is established that the first criterion was accomplished since the students mean score of post-test was 9,43 points higher than the mean score of students’ pre-test, from 66,86 on pre-test become 74,19 on the post-test. The second criterion of success is when there were more than 60% students could pass minimum standard score of English that is 75. This is achieved since the students that could pass minimal standard score of English was 64,86%.